OUTCOME BASED-EDUCATION (OBE) QUALITY MANAGEMENT SYSTEM - MIZANA I, AMER (Universiti Malaysia Sarawak, (UNIMAS), 2018)
This project is basically focused on the development of web application software for managing the quality of education process basis on the education outcome (OBE). The web application software is designed and implemented for the use of academic staffs of Faculty of Engineering in UNIMAS. With the use of this software, the faculty can easily assess the contents of the OBE implementation and improve its effectiveness by monitoring the students’ performances. The significant of the project is not only to assist in facilitating the users but to ensure the standardization of OBE implementation in Faculty of Engineering, UNIMAS.